(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2023)
This article explores Chile’s economic trajectory through the lens of its free-market experiment, focusing on the tangible impact on growth within the real sector. Drawing on a variety of reputable sources, the author analyzes the evolution of Chile’s economic landscape, emphasizing the pivotal shift from protectionist policies to a market-oriented approach during the 1970s. The article delves into the intricacies of market liberalization and global integration, substantiating claims with trade data from the World Trade Organization (WTO) and GDP growth statistics from the World Bank.